2023
DOI: 10.1177/11782218231172054
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Recreational Cannabis Legalization on Cannabis Use and Associated Outcomes: A Systematic Review

Abstract: Background: Recreational cannabis legalization has become more prevalent over the past decade, increasing the need to understand its impact on downstream health-related outcomes. Although prior reviews have broadly summarized research on cannabis liberalization policies (including decriminalization and medical legalization), directed efforts are needed to synthesize the more recent research that focuses on recreational cannabis legalization specifically. Thus, the current review summarizes existing studies usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 105 publications
0
9
0
4
Order By: Relevance
“…Treatment retention was comparable to previous studies but low, and moderate levels of treatment satisfaction were observed. Within the context of several countries having legalized cannabis use (or considering doing so), there is growing need for an effective treatment for CUD (although it should be noted that the relationship between legalization and drug use appears to be complex, and while some evidence suggests legalization may be associated with increased cannabis use findings are inconsistent and it is currently unclear whether legalization has accelerated rates of CUD or increased treatment demand 40 - 42 ). This retrospective study provides preliminary evidence to support the use of this intervention in a novel group setting, although with the caveat that this study is limited by missing data and high attrition, and these findings remain to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment retention was comparable to previous studies but low, and moderate levels of treatment satisfaction were observed. Within the context of several countries having legalized cannabis use (or considering doing so), there is growing need for an effective treatment for CUD (although it should be noted that the relationship between legalization and drug use appears to be complex, and while some evidence suggests legalization may be associated with increased cannabis use findings are inconsistent and it is currently unclear whether legalization has accelerated rates of CUD or increased treatment demand 40 - 42 ). This retrospective study provides preliminary evidence to support the use of this intervention in a novel group setting, although with the caveat that this study is limited by missing data and high attrition, and these findings remain to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Several countries, including Canada, Uruguay, and Malta, have taken the bold step to legalize recreational cannabis at the national level. In contrast, others, such as Georgia, Germany, Luxembourg, Mexico, South Africa, Thailand, and the United States, have also moved toward legalization to varying extents [28]. The impact of marijuana legalization in different countries has been a topic of heated debate, with concerns raised about potential repercussions such as lower educational achievement among teens [25].…”
Section: Comparison With Countries That Have Legalized Marijuanamentioning
confidence: 99%
“…Additionally, Peru, Germany, New Zealand, and the Netherlands, along with numerous U.S. states, have legalized medical use of cannabis. The only three nations that have nationalized the use of cannabis for recreational purposes are Canada, Uruguay, and Malta [ 3 ]. Cannabis possession is prohibited in the U.S. unless it is intended for authorized research purposes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis possession is prohibited in the U.S. unless it is intended for authorized research purposes [ 4 ]. However, individual U.S. states started legalizing marijuana for recreational use in 2012, and by 2023, nearly half of all U.S. states have followed suit [ 3 ].…”
Section: Introductionmentioning
confidence: 99%